2016
DOI: 10.1002/pat.3888
|View full text |Cite
|
Sign up to set email alerts
|

Gradient polymer networks formed by photopolymerization with self‐floating polysiloxane‐containing nanogel

Abstract: Polysiloxane‐containing nanogels can be used as a fast, convenient and environmentally friendly method to control gradient photopolymerization and to obtain gradient polymer network because of its self‐floating feature. The chain length of polysiloxane is a key factor that influences the self‐floating capability of the polysiloxane‐containing nanogel. This paper reports a series of nanogels compositions synthesized with methacrylate‐modified polysiloxanes with different chain lengths, urethane dimethacrylate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…D2 additive contains polysiloxane copolymer, which is more effective in preventing floating. It contains silicone, which helps to prevent Bernard vortex and streaks, which improves the surface smoothness [40]. When the wetting and dispersing agent D1 with an amount of 0.8% and D2 with an amount of 0.4% are added, the surface of the paint film is most uniform and smooth.…”
Section: Selection and Effects Of Wetting And Dispersing Agentsmentioning
confidence: 99%
“…D2 additive contains polysiloxane copolymer, which is more effective in preventing floating. It contains silicone, which helps to prevent Bernard vortex and streaks, which improves the surface smoothness [40]. When the wetting and dispersing agent D1 with an amount of 0.8% and D2 with an amount of 0.4% are added, the surface of the paint film is most uniform and smooth.…”
Section: Selection and Effects Of Wetting And Dispersing Agentsmentioning
confidence: 99%
“…In the polymerization process, the volumetric shrinkage occurs during crosslinking of the polymeric system and depends on the chemical composition and polymerization reaction. Previously, it was reported that various strategies are applied to reduce the volumetric shrinkage, involving the use of nanoparticle-photopolymer composites [10], liquid crystalline monomers [11], radical/cationic hybrid initiating systems [12], thiol-ene cross-linked systems [13], and nanogels [14].…”
Section: Introductionmentioning
confidence: 99%